(untitled) (Journal of Innovative Research, 2025)
This study assessed TB prevalence and factors affecting screening among household contacts in Ga West Municipality, Ghana. A cross-sectional descriptive study was conducted with 107 household contacts of TB index cases identified from health facility records. A structured questionnaire collected data on demographics, TB knowledge, screening, and treatment status. Utilizing STATA 14, the statistical analysis included descriptive statistics and Pearson chi-square tests, with a significance level set at p < 0.05. The mean age of participants was 35.7 years (SD ± 11.8), predominantly male (58.9%) and urban dwellers (78.5%). Of the participants, 57.9% were screened for TB, with a positive rate of 20% (n=9). Among those diagnosed, 88.9% (n=8) initiated treatment. Awareness of TB was high (90.7%), yet only 6.7% could identify five key symptoms of TB. Significant associations were found between educational level and TB awareness (χ²(4) = 17.237, p = 0.002), between residence and screening likelihood (χ²(1) = 4.26, p = 0.039), and individuals residing within 5 km of a health facility had a higher likelihood of being screened compared to those living farther away (χ²(1) = 10.41, p = 0.001). This study found that despite high awareness of TB transmission, screening rates among household contacts were low; enhanced outreach and education efforts are needed to improve knowledge and screening, particularly for urban residents. The predominance of male pulmonary cases was noted, highlighting the necessity for targeted efforts to mitigate TB transmission and further research on barriers to screening.